Analysis of Blood Lead Levels on Street Vendors at Terminal Kampung Rambutan - Sofyan, Nusaibah; Wintarsih, Ietje; Ismail, Ahyar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Emissions of motor vehicles containing heavy metals, one of which is lead (Pb). Street vendors belong to the community group at a high risk of exposure to motorized vehicle emissions. This study aims to analyze and assess lead levels in the blood of street vendors. The research design used was cross-sectional with a method of collecting data through observation, interviews, and questionnaires. Lead measurement using the Atomic Absorption Spectrophotometer (AAS) method. The sample was determined by a purposive sampling method of 30 street vendors. The results of this study are 18 respondents (60%) with blood lead levels exceeding normal levels namely